Using 3D Scanners for Designing Peristaltic Hands: Advancements in Prosthetic Technology - Azizbek Yusufov (Genius Journals, 2023)
Prosthetic technology has made significant progress in recent years. It aims to improve the quality of life and functionality of people with missing limbs. Among these innovations, the integration of 3D scanning technology has emerged as a promising approach to design prosthetic hand, a type of prosthetic arm that mimics the natural movement of the human hand through peristaltic movements. This thesis explores the utility and effectiveness of 3D scanners in the design and customization of peristaltic arms, exploring their potential to create highly customizable and functional prosthetic devices.
Keywords: Prosthetic hand; 3D scanning technology; Prosthetic technology